The Comparison Effect of Electrical Cigarrete and Conventional Cigarrete Smoke toward White Rat’s (Rattus norvegicus) Lung Histopathology - Yoan Asri Triantara; Inggit Almira; Sarwan Adi Kusumo; Muhammad Fajar; Dicky Darmawan; Dwi Winarni (Jurnal Respirologi Indonesia, 2019)
Background: The number of cigarettes smoked per day has an average of 12,3% of cigarettes in 2013. The increase of the conventional cigarettes price in 2016 made some conventional smokers switch to electrical cigarettes because more safety than conventional One of the indicators of pulmonary damage is the increase of alveolar macrophage that cause pulmonary structural change triggered by substances in the cigarette. Methods: Thirty two of white rat were divided into four groups (control, conventional cigarette, electrical cigarette with 0 miligram (mg) nicotine, and electrical cigarette with 3 mg nicotine) and were exposed for 35 days (30x2 minutes; in the morning and evening). Results: The group exposed to conventional cigarette smoke has the highest average number of macrophages than the cigarette smoke group with nicotin levels of 0 mg, electric cigarette with 3 mg nicotine and control. Brown Forsythe test continued with Games-Howell post hoc test indicates that there are significant mean difference between each group except between group exposed to electric cigarette smoke with 3 mg nicotine and exposed to conventional cigarette smoke. Based on the indicator assumption of lymphoid infiltration and thickening and fusion of the alveolar, the smoke of conventional cigarette and electric cigarette with 3 mg nicotine caused more histopathological damage to the white rat’s lungs than of conventional cigarette than the smoke of electric cigarette with 0 mg nicotine and those in the control group. Conclusion: The exposure of conventional cigarette smoke caused the highest damage to Rattus norvegicus’ pulmo according to macrophage alveolar and histopathological indicator, but not significantly different with the exposure of electrical cigarette with 3 mg nicotine. The exposure of electrical cigarette with 0 mg nicotine caused minor damage equals to control group based on histopathological indicator. (J Respir Indo 2019; 39(2): 88-91)